2021
DOI: 10.3390/epidemiologia2030022
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mobility and Sanitary Measures on the Delay of Community Transmission of COVID-19 in Costa Rica

Abstract: The aim of this paper is to infer the effects that change on human mobility had on the transmission dynamics during the first four months of the SARS-CoV-2 pandemic in Costa Rica, which could have played a role in delaying community transmission in the country. First, by using parametric and non-parametric change-point detection techniques, we were able to identify two different periods when the trend of daily new cases significantly changed. Second, we explored the association of these changes with data on po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…We did not know for sure if and how effective these sanitary measures were at reducing human mobility. We performed a parallel analysis ( Barboza et al, 2021 ) describing the impact that reduction in mobility had on infections and hospitalization. However, we also anticipated that the same intervention imposed at different pandemic stages was unlikely to produce the same results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not know for sure if and how effective these sanitary measures were at reducing human mobility. We performed a parallel analysis ( Barboza et al, 2021 ) describing the impact that reduction in mobility had on infections and hospitalization. However, we also anticipated that the same intervention imposed at different pandemic stages was unlikely to produce the same results.…”
Section: Discussionmentioning
confidence: 99%
“… Protective measures. Previous studies ( Chu et al, 2020 , Cook, 2020 , Barboza et al, 2021 ) have shown that incorporating appropriate personal protective measures and restricting human mobility reduce the probability of infection. If a particular interaction between two nodes involves using personal protective measures, then we reduce the probability accordingly; see Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Como era previsible, tal mejora fue efímera: a partir de junio de 2020, los contagios empezaron a aumentar, una vez que el Poder Ejecutivo flexibilizó las restricciones en respuesta a las presiones de los empresarios. Además, las medidas adoptadas para enfrentar la crisis favorecían de manera desproporcionada a los patronos, facultados para reducir salarios y jornadas de modo unilateral (Barboza, 2021;Muñoz y Chacón, 2020, pp. 12-14).…”
Section: )unclassified
“…Nevertheless, interest in many works has focused on the impact of COVID-19 on mobility, and few efforts have been directed at assessing how regulating mobility rates can have positive effects on controlling virus transmission. Examples of these studies have focused on Taiwan [ 6 ], Poland [ 7 ], the United States [ 8 ], India [ 9 ], Spain [ 10 , 11 ], Japan [ 12 ], the United Arab Emirates [ 13 ], Saudi Arabia [ 14 ], Greece [ 15 ], China [ 16 , 17 ], Indonesia [ 18 ], Austria [ 19 ], Italy [ 20 ], Portugal [ 21 , 22 ], South Africa [ 23 ], Costa Rica [ 24 ], and Australia [ 25 ], among others.…”
Section: Introductionmentioning
confidence: 99%